Prehipertensión: la influencia del estrés psicológico en adolescentes. - Romero, Vanessa; Silva, Eglé; Villasmil, José; Bermúdez, Greily; Madueño, Freddy (Investigación Clínica, 2017)
Ver Resumen PDF.